Evaluation of Hematological Parameters in the Genetic Prospective in Epileptic Patients of Khyber Pakhtunkhwa - Farooq N; Ali N; Ullah S (Dove Medical Press, 2019)
Nazish Farooq,1,2 Niaz Ali,3 Shakir Ullah3,4 1Department of Hematology, Institute of Basic Medical Sciences, Khyber Medical University, Peshawar, Pakistan; 2Department of Pathology, Khyber Medical College, Peshawar, Pakistan; 3Department of Pharmacology, Institute of Basic Medical Sciences, Khyber Medical University, Peshawar, Pakistan; 4Department of Pharmacy, University of Malakand, Chakdara, PakistanCorrespondence: Niaz Ali; Shakir UllahDepartment of Pharmacology, Institute of Basic Medical Sciences, Khyber Medical University, Peshawar, PakistanEmail niazpharmacist@yahoo.com; shakir.ibms@kmu.edu.pkBackground: Epilepsy is a treatable disease, but unfortunately a treatment gap exists in epileptic patients, especially in developing countries, due to adverse effects of antiepileptic drugs and polymorphisms in genes. Carbamazepine is the most commonly used medication in epilepsy, but is related to some serious and rare adverse effects. The aim of the study was to investigate the effect of folate metabolizing genes (MTHFR and DHFR) polymorphisms on different parameters of complete blood count in patients who were treated with carbamazepine and valproic acid.Materials and methods: Blood samples from 267 epileptic patients were collected on consent and surrogate consent forms. The blood was analyzed for changes in different parameters in complete blood count through a blood analyzer. The MTHFR gene was genotyped using the RFLP method. The data were analyzed using GraphPad Prism 6.Results: The homozygous mutant genotype (677CT) of the methylenetetrahydrofolate reductase enzyme (MTHFR C677T) gene significantly affects the level of hemoglobin (P=0.12), hematocrit (P=0.008) and mean corpuscular hemoglobin (P=0.01) compared to the homozygous wild genotype (677CC) and heterozygous mutant genotype (677CT) of the MTHFR (C677T) gene. However, the heterozygous genotype (1298AC) of MTHFR (A1298C) gene affect the total leukocyte count (P=0.037) level significantly.Conclusion: Changes in different parameters of complete blood count were statistically significant but clinically insubstantial decreases in different parameters of complete blood count indexes.Keywords: AEDs, epilepsy, complete blood count, carbamazepine, MTHFR gene, DHFR gene